Prefo and Social Trust in The Du-Hope Barter System of Lamalera Community - Konradus, Blajan; Dasion, Agustinus Raja (Universitas Negeri Semarang, 2021)
The objectives of this study are (1) to describe the barter du-hope tradition as a traditional Lamalera exchange system of goods in a subsistence economic system, (2) to explain the barter du-hope tradition resulting in a new kinship competition (prefo) based on mutual trust between communities. This study uses ethnographic methods to be able to get emic of the du-hope barter system. The study was conducted in four villages, namely Lamalera, Wulandoni, Puor and Labalimut. The results showed two main theses. First, the barter du-hope tradition is the economic defence system of the local community. Barter du-hope became the food security system of the Lamalera coastal community and the mountain community. Secondly, du-hope barter transactions create new relationships built on strong social trust. Prefo is a new kinship like family (outside of biological kinship) built on mutual trust between the people of Lamalera and other communities in the mountain area. Social trust is created by exchanging and sharing food items and building joint needs. Preference is a complete moral relationship with a sense and desire to help one another. This research provides support for the development of the local economy by providing support and space for the protected system of the barter du-hope Lamalera, which is now being threatened by the capitalist economic system and the global market.